High Vacuum Deposition of Biferrocene Thin Films on Room Temperature Substrates - Leber,R; Wilson,LE; Robaschik,P; Inkpen,MS; Payne,DJ; Long,NJ; Albrecht,T; Hirjibehedin,CF; Heutz,S (Chemistry of Materials, 2017)
Metallocenes are a promising candidate for future spintronic devices due to their versatile and tunable magnetic properties. However, single metallocenes, e.g., ferrocene, sublimate below room temperature, and therefore the implementation for future applications is challenging. Here, a method to prepare biferrocene thin films using organic molecular beam deposition (OMBD) is presented, and the effect of substrate and deposition rate on the film structure and morphology as well as its chemical and magnetic properties is investigated. On Kapton and Si substrates, biferrocene interacts only weakly with the substrate, and distinct grains scattered over the surface are observed. By incorporating a 3,4,9,10-perylenetetracarboxylic dianhydride (PTCDA) seeding layer and depositing biferrocene at high deposition rates of 1.0 Å s–1, it is possible to achieve a well-ordered densely packed film. With spintronic applications in mind, the magnetic properties of the thin films are characterized using superconducting quantum interference device (SQUID) magnetometry. Whereas initial SQUID measurements show weak ferromagnetic behavior up to room temperature due to oxidized molecule fragments, measurements of biferrocene on PTCDA capped with LiF show the diamagnetic behavior expected of biferrocene. Through the successful deposition of biferrocene thin films and the ability to control the spin state, these results demonstrate a first step toward metallocene-based spintronics.